Emerging Roles for MicroRNAs in Perioperative Medicine. (February 2016) - Neudecker, Viola; Brodsky, Kelley S.; Kreth, Simone; Ginde, Adit A.; Eltzschig, Holger K.
Abstract : MicroRNAs (miRNAs) are small, non–protein-coding, single-stranded RNAs. They function as posttranscriptional regulators of gene expression by interacting with target mRNAs. This process prevents translation of target mRNAs into a functional protein. miRNAs are considered to be functionally involved in virtually all physiologic processes, including differentiation and proliferation, metabolism, hemostasis, apoptosis, and inflammation. Many of these functions have important implications for anesthesiology and critical care medicine. Studies indicate that miRNA expression levels can be used to predict the risk for eminent organ injury or sepsis. Pharmacologic approaches targeting miRNAs for the treatment of human diseases are currently being tested in clinical trials. The present review highlights the important biological functions of miRNAs and their usefulness as perioperative biomarkers and discusses the pharmacologic approaches that modulate miRNA functions for disease treatment. In addition, the authors discuss the pharmacologic interactions of miRNAs with currently used anesthetics and their potential to impact anesthetic toxicity and side effects. Abstract : MicroRNAs are small, noncoding RNA molecules that have the capability to regulate protein expression at the posttranslational level. They play important roles as modulators of various biological functions including health and disease. This review provides an overview of microRNA biology, and specifically highlights their functional roles for the field of perioperative medicine.